NARRATIVE OF DA'WAH ON MEDIA ACCOUNTS: NARRATIVE ANALYSIS OF DA'WAH MESSAGES ON SOCIAL MEDIA ACCOUNTS - Kholid Noviyanto (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2024)
Abstrac: : The development of the media in the era of generation z has greatly influenced the development of Islamic da'wah, especially in the narrative of da'wah messages as the antithesis of the conservative, liberalist, and radical Islamic narrative which has recently become a public discussion with the rise of cases of religious discrimination, the emergence of intolerant narratives. Therefore, this study wants to reveal the narrative of moderate Islam. This research was conducted by the researcher using a qualitative method with a narrative approach. The data collection technique is carried out through documetry and observation of non-participants to obtain accurate data. There are two types of data sources, namely primary sources in the form of dakwah_islam_wastiyah instragram media accounts and secondary sources in the form of literature books and scientific articles that support this research. This study was also analyzed using narrative analysis including the interpretation of the meaning of the narrative of tolerance values on Instagram media accounts with results showing that the narrative of moderate da'wah messages on dakwah_islam_wasatiyah accounts found five narratives related to wasatiyah Islamic values which include first, solidarity narratives, second, gentleness in da'wah, and third, human love for other humans. The fourth is the prohibition of prejudice, the fifth is the prohibition of degrading other